Pengaruh Kepemimpinan Yang Dinamis Dalam Memajukan Organisasi Muhammadiyah Di Kabupaten Luwu - Sri lestari; Samsul Bachri; Sari Ratna Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Leadership is able to influence employees to work with maximum quantity and quality of work to achieve organizational goals. Etymologically, Muhammadiyah comes from Arabic, from the Kata "محـمد" which is the name of the last Prophet and Messenger of Allah. Muhammad himself means "the praiseworthy". This study aims to analyze the influence of dynamic leadership on the development of Muhammadiyah in Luwu Regency, identify supporting and inhibiting factors in the application of this leadership style, and provide recommendations for strategies that can be applied to improve the effectiveness of leadership in Muhammadiyah. By understanding the influence of dynamic leadership, it is hoped that Muhammadiyah can continue to develop and contribute more to the community in Luwu Regency.This study is a quantitative research with a survey using a questionnaire aimed at the cadres of Muhammadiyah organizations in Luwu Regency.The sample population in this study was carried out using the purpose sampling technique with a sample of 80 respondents. The data analysis techniques used in this study are descriptive statistical analysis, validity and reality test, normality test and simple linear regression using the help of SPSS IBM 20.The results of this study show that dynamic leadership has a significant effect on the progress of the Muhammadiyah organization in Luwu Regency.